Is surgical treatment necessary in all hydronephrotic kidney allografts? - Topuzović, Čedomir; Radovanović, Milan N; Pejčić, Tomislav (Vojnosanitetski pregled, 2020)
Background/Aim. The management of kidney graft hydronephrosis (KGH) is usually surgical, although some cases require expectant management and follow-up. The aim of the study was to discuss the criteria for expectant management or immediate surgical intervention in the series of patients with KGH. Methods. The paper is based on a retrospective study of 42 patients with KGH. The patients underwent kidney transplantation from January 2007 to December 2012. There were 19 cadaveric donor recipients and 23 living donor recipients. The average follow-up was 15,2 (range 12–21) months. The average recipient`s age was 41,6 years. In every case study, the diagnosis of graft hydronephrosis was established using abdominal ultrasonography. The degree of hydronephrosis was estimated on the basis of measuring the maximal diameter of the pelvicalyceal dilatation (PD). Results. There were no patients with graft failure after the period during which they were under medical observation. Hydronephrosis resolved completely in six (14%) patients. The median maximal PD was 28 ± 9 (range 14 –38) mm and the median last PD was 23 ± 11 (range 0–35) mm and they did not differ significantly (p = 0.23). The last serum creatinine was significantly lower than the maximal creatinine value (p < 0.05). In twelve (29%) patients renal function normalized. Renal function remained stable during the period of medical observation. At the end of the follow-up, all patients had sterile urine culture. Conclusion. The traditional doctrine, according to which KGH represents an absolute indication for surgery, can be debated; the majority of the patients observed require just active surveillance. Prompt surgical correction is recommended only in cases with increasing pelvicalyceal dilatation and the development of symptoms, progressively decreasing renal function or recurrent urinary tract infection.
Keywords: kidney transplantation; postoperative complications; hydronephrosis; kidney function tests; prognosis; conservative treatment